Simultaneous multigene integration in Aspergillus fumigatus using CRISPR/Cas9 and endogenous counter-selectable markers - Luis Enrique Sastré-Velásquez; Natalia Mach; Birte Mertens; Alexander Kühbacher; Petra Merschak; Alex Dallemulle; Lukas Lechner; Clara Baldin; George Diallinas; Fabio Gsaller (Journal of Biological Engineering)
Abstract Background The discovery of CRISPR/Cas9 and its subsequent accessibility in daily research initiated a new era in genome editing. This game-changing genetic instrument enabled a vast array of challenging applications requiring site-specific genome engineering as well as applications involving the equipment of cells with additional genetic traits. Despite the undisputed benefits of this technology, for facile and efficient selection of successfully manipulated cells selectable markers remain indispensable. Over the past years endogenous counter-selectable markers have come into focus in antifungal research enabling site-directed integration of multiple genes into the genome of the human mold pathogen Aspergillus fumigatus. However, gene cassettes had to be transformed in a consecutive manner keeping multigene integrations laborious and time-consuming. Results In this work, we coupled the use of CRISPR/Cas9 with endogenous counter-selectable markers to achieve the simultaneous integration of multiple expression cassettes. The three markers used in this work included the herein employed azgA and the previously identified fcyB and cntA, responsible for 8-azaguanine, 5-fluorocytosine and 5-fluorouridine uptake, respectively. Exploiting their role in uptake of different selective agents, a triple selective transformation procedure and genomic integration of three expression cassettes in A. fumigatus was successfully accomplished. In addition to three distinct cellular reporters, we introduced strain-specific fluorescent reporters into four isolates displaying different levels of antifungal azole resistance to subsequently visualize and monitor their growth patterns in the same growth environment. Conclusions The technology described in this study significantly streamlines the genetic manipulation process, reducing both time and labor associated with sequential transformations. By enabling the introduction of multiple genetic traits in a single transformation event, this strategy provides a flexible and efficient platform for a wide range of applications. As such, it enhances the potential for rapid and effective multigene integration, advancing the field of genetic engineering in fungi.